Kidney biopsies in Kinshasa: Epidemiology and histopathology - Buanza, Rive LUKUAKU; Ali, Fabrice BUMWANA; Kouandzi, Mignon Dreude PANDI; Ngoyi, Nathan KALONJI; Mukatshing, Josué KAPATA; Ngwabaña, Augustin KOBONGO; Ngabo, Welcome KWEREKWA; Tasema, David AZAKO; Lolangwa, Fabrice BOKABAMDJA; Niombo, Thierry MAKETO; Mutombo, Olivier TSHINGOMBE; Mbelu, Marie-Paul MBOMBO; et al. (Orapuh Journal, 2025)
Introduction Renal biopsy (Renal Puncture Biopsy, RPB) is essential for the diagnosis and prognosis of kidney disease. However, it is rarely performed in African countries, particularly in French-speaking regions, despite its importance for assessing disease progression and guiding treatment. Purpose To determine the epidemiological and histopathological profiles of kidney biopsies in Kinshasa from 2020 to 2022. Methods This retrospective cross-sectional study was conducted across various laboratories in Kinshasa and covered the period from January 2020 to December 2022. Results Among the 1,642 biopsies performed between 2020 and 2022 at Kinshasa University Clinic (KUC), Nganda Center (NC), and the National Institute for Biomedical Research (NIBR), only 51 were renal biopsies, representing 2% (n = 51). The most represented age group was 38–47 years (35%). Men accounted for 67.7% of cases. Nephrotic syndrome was the most common clinical indication (39.2%). Segmental and focal hyalinosis predominated histologically, accounting for 45.1% of cases. Conclusions Although infrequent in our setting, renal biopsies remain indispensable when kidney disease is suspected. They constitute a critical tool in the nosological, diagnostic, and therapeutic approach to nephrology for the effective management of kidney disease.